The system of training of personnel with secondary special, vocational education for the agricultural sector in Karakalpak stan (Global Scientific Review, 2023)
This article focuses on the information about the training of agricultural workers who were captured during the independence period in Karakalpakstan. Among them, the issues of training of personnel with secondary vocational education in the field of agricultural economy, opening of secondary vocational colleges and the training of agrarian specialists there are three opportunities that have been opened. provided information about it.